Analisis Anggaran Dan Realisasi Terhadap Pengelolaan Dana Bos di SMA Negeri 1 Sitiung - Annisa Rahma Asfitrin (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research evaluates the alignment between the budget and the realization of the School Operational Assistance (BOS) funds in SMA Negeri 1 Sitiung with Articles 13 and 14 of the Minister of Home Affairs Regulation Number 62 of 2011. The study is conducted at SMA Negeri 1 Sitiung, West Sumatra Province. Primary and secondary data serve as the information sources. The research method employed is qualitative descriptive, comparing practices with theory, and concluding findings in a thesis. The results indicate that the management of BOS funds in SMA Negeri 1 Sitiung complies with the applicable BOS guidelines, referring to the Minister of Education and Culture Regulation Number 6 of 2021. The reporting of BOS funds in the school is comprehensive and detailed, ensuring accountability to the government and avoiding issues of delayed disbursement and BOS.